"Other" possibilities? Assessing regional and extra-regional dental affinities of populations in the Portuguese Estremadura to explore the roots of Iberia's Late Neolithic-Copper Age. (February 2017) - Irish, Joel D.; Lillios, Katina T.; Waterman, Anna J.; Silva, Ana M.
Abstract: The relationship between the development of social complexity in the Iberian Peninsula during the 4th and 3rd millennia BCE (Late Neolithic and Copper Age) and population movement has been a longstanding question. Biological affinity analyses were used to explore Iberian demographic dynamics, and specifically, to discern whether there is evidence for migration and gene flow between northwest African, eastern Mediterranean, and Iberian populations. Affinities based on comparisons of nonmetric traits from the Arizona State University Dental Anthropology System were estimated among samples of burial populations from three key Late Neolithic-Copper Age sites in the Portuguese Estremadura: Cova da Moura (3700–2300 BCE), Bolores (2800–2600 BCE), and Pai Mogo I (2800–2600 BCE). Results indicate: 1) the possibility of genetic exchange with African and other Mediterranean peoples, 2) some measure of population continuity over time in the Estremadura, and 3) possible local isolation of populations, given distinctive patterning at the site of Pai Mogo, located 23 km north of Cova da Moura and Bolores. Highlights: Iberian Late Neolithic/Copper Age social complexity may be of extra-regional origin. Dental affinity analyses were conducted on three human samples from Portugal. The three were compared with eastern Mediterranean and Northwest African samples. Outside genetic influence in Late Neolithic/Copper Age Portuguese is possible. Dental heterogeneity among Portuguese samples may be from reproductive isolation.